English Teachers? Readiness and Challenges in Implementing ICT-Integrated 21st Century Skills - Khilda Shopia; Aisha Nadya; Tenia Ramalia; Heni Cahya Ramdani (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2026)
This study investigated English teachers? readiness and challenges in implementing ICT-integrated 21st century skills in English language teaching. A descriptive quantitative and qualitative research design was used to conduct this research. Data was collected from 50 English teachers through a 15-item Likert-scale questionnaire. The findings illustrate that teachers demonstrate a moderate level of readiness, including adequate technological knowledge, positive attitudes, and confidence in using digital tools. However, some challenges hinder effective implementation, such as limited technological facilities, insufficient training, lack of institutional support, time constraints, technical issues, and varying levels of students? digital literacy. The study concludes that institutional support, professional development, and adequate infrastructure are essential to support effective ICT integration.